Attitudes towards the use of fluorides for oral health among Islamic clerics in Kelantan province, Malaysia - Nazita, Y.; Jaafar, N.; Doss, J.G.; Rahman, M.M.A. (2013)
Objective: To assess the knowledge, attitudes and practices of Imams (Islamic clerics) concerning fluoride toothpaste and fluoridated water to improve oral health in Kelantan. Basic research design: Cross sectional study of Imams in 65 registered mosques in Pasir Puteh district, Kelantan. Method and participants: Face-to-face interview, using structured questionnaire and some open ended questions. Results: Most of the 83 interviewees (82 participation rate) were unsure whether their toothpaste contained fluoride (64), only 25 were sure. More than one-third (37) were using fluoridated piped water. Most (87) had little knowledge of fluorides and more than two-thirds (69) had lacked positive attitudes towards its use. Television (54) was the most common source of information about fluorides, followed by newspapers (9). The main reasons given among the few who opposed fluoride use were i) fear of dangerous side effects (4) and ii) uncertainty about the halal status of fluoride (2), Attitudes were not associated with the use of fluoridated water supply (p=0.999), age (p=0.103), income (p=0.540) and location (p=0.999). Conclusion: Over two-thirds of Imams had little knowledge of and lacked positive attitudes towards fluoride use in toothpaste and piped water supplies.